Differences in Behavior of Nutrition Fulfillment In Mothers of Toddlers Aged 24-47 Months - Nisaa'i Ramilinia Panuluh; Ristya Widi Endah Yani; Ari Tri Wanadyo Handayani (Universitas Islam Jember, 2023)
Nutritional problems in toddlers usually occur because toddlers experience appetite disorders, disorders of the digestive organs, and inadequate nutritional intake in quantity and quality. The most influential factor comes from the mother, namely behavior in fulfilling nutrition, which includes knowledge, actions, and attitudes in choosing nutritional intake so that it can affect the nutritional condition of toddlers. The purpose of this study was to analyze the differences in the behavior between mothers with malnourished toddlers and mothers with well-nourished toddlers in fulfilling nutrition for toddlers aged 24-47 months. This study used analytical observational design with cross sectional approach. The number of respondents is 33 mothers with malnourished toddlers and 33 mothers with well- nourished toddlers. The results of the Mann Withney U test showed that p-value was less than α in knowledge (P- value = 0.000), attitudes (P-value = 0.004), actions (P-value = 0.000), and behavior (P-value = 0.000). Based on these results, it can be concluded that there are differences in behavior (knowledge, attitudes, and actions) between mothers with malnourished toddlers and mothers with well-nourished toddlers in fulfilling nutrition for toddlers aged 24-47 months.